Solute clustering and supersaturated solid solution of AlSi10Mg alloy fabricated by selective laser melting - Takashi Maeshima; Keiichiro Oh-ishi (Heliyon, 2019)
α-Al grains surrounded by Al-Si eutectic as the substructures in AlSi10Mg alloy fabricated by selective laser melting (SLM) were investigated in detail using three-dimensional atom-probe and transmission electron microscopy. Quantitative analysis of α-Al revealed (1) the formation of Mg clusters and Mg-Si co-clusters with a density in the order of 1023 /m3 in α-Al of the as-built state caused by the complicated thermal history, and (2) a supersaturated Si content that significantly exceeded the maximum solubility due to rapid solidification, during the SLM process.